PERMODELAN SUMBERDAYA BIJIH NIKEL BERDASARKAN METODE GEOSTATISTIK DI DESA BONI KABUPATEN RAJA AMPAT PAPUA BARAT - Ricardo O.M. Hutapea (INTAN Jurnal Penelitian Tambang, 2019)
Estimating of nickel resource in block WN-01 PT. Karunia Alam Waigeo, West Papua aim to understand the number of metal tonnages and the direction of the resource dispersion. The study has been done with phases which are literature study, retrieval of drill data (49 bore holes), data processing with Ordinary Kriging (OK) method using GS+ version 70 software, in as much, estimating the resources by means of block method kriging and point kriging. To understand the estimation correlation of grade to composite grade the scatter diagram analysis was used. Based on scatter diagram (scatter plot) for block kriging method correlation coefficient of 0,8843 is obtained while for point kriging method is 0,8935. With the standard deviation of 0,3280, the point block kriging method has obtained 18.630,08 tons of nickel while for point kriging method with 0,4060 of the standard deviation the nickel obtained is 18.875,41 tons.